2022
DOI: 10.3389/fmicb.2022.977337
|View full text |Cite
|
Sign up to set email alerts
|

Improving prodigiosin production by transcription factor engineering and promoter engineering in Serratia marcescens

Abstract: Prodigiosin (PG), a red linear tripyrrole pigment produced by Serratia marcescens, has attracted attention due to its immunosuppressive, antimicrobial, and anticancer properties. Although many studies have been used to dissect the biosynthetic pathways and regulatory network of prodigiosin production in S. marcescens, few studies have been focused on improving prodigiosin production through metabolic engineering in this strain. In this study, transcription factor engineering and promoter engineering was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Another study analyzing the endogenous constitutive promoter of S. marcescens JNB5-1 using RNA-Seq revealed that the highly active promoters were primarily associated with outer membrane proteins and ribosomal subunit proteins, with the most active one found in the 50S ribosomal subunit protein L10. 37 Strain-to-strain variability in promoters may arise from the −35 and −10 motifs within the promoter, untranslated sequences preceding the ATG start site, or strain specificity, as the quantitative and qualitative expression of transcription factors exhibit strain-dependent differences. 38,39 Xylose, the second most abundant sugar in nature, after glucose, serves as a renewable resource for bacteria to produce various secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study analyzing the endogenous constitutive promoter of S. marcescens JNB5-1 using RNA-Seq revealed that the highly active promoters were primarily associated with outer membrane proteins and ribosomal subunit proteins, with the most active one found in the 50S ribosomal subunit protein L10. 37 Strain-to-strain variability in promoters may arise from the −35 and −10 motifs within the promoter, untranslated sequences preceding the ATG start site, or strain specificity, as the quantitative and qualitative expression of transcription factors exhibit strain-dependent differences. 38,39 Xylose, the second most abundant sugar in nature, after glucose, serves as a renewable resource for bacteria to produce various secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The strong promoters obtained were primarily found in lipoproteins, and the most potent one was promoter P6 of outer membrane lipoproteins. Another study analyzing the endogenous constitutive promoter of S. marcescens JNB5‐1 using RNA‐Seq revealed that the highly active promoters were primarily associated with outer membrane proteins and ribosomal subunit proteins, with the most active one found in the 50S ribosomal subunit protein L10 37 . Strain‐to‐strain variability in promoters may arise from the −35 and −10 motifs within the promoter, untranslated sequences preceding the ATG start site, or strain specificity, as the quantitative and qualitative expression of transcription factors exhibit strain‐dependent differences 38,39 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to screening and selecting S. marcescens strains with high Pg synthesis capabilities and optimizing culture environments and conditions, a stronger approach to enhancing gene expression at the transcriptional level is currently of interest, such as promoter techniques or modifying certain unfavorable factors for the Pg synthesis pathway. In this regard, Pan et al (2022) enhanced the Pg synthesis capability of S. marcescens JNB5-1 by mutating the regulatory factor OmpR that affects Pg synthesis. The authors created a mutation library by randomly inserting transposons and screened for a mutant strain with a 1.6fold increase in Pg synthesis yield.…”
Section: Introductionmentioning
confidence: 99%
“…The two component system EnvZ/OmpR is an important signal transduction system in bacteria responding to various environmental stress and growth conditions ( Qin et al, 2001 ). We have previously demonstrated that when envZ or ompR was knocked out, S. marcescens FZSF02 lost its prodigiosin biosynthesis ability ( Jia et al, 2021 ), and OmpR was also recently found to control prodigiosin biosynthesis in S. marcescens JNB5-1 ( Pan et al, 2022 ). However, the regulatory mechanism of the two-component EnvZ/OmpR system on prodigiosin production is still unknown.…”
Section: Introductionmentioning
confidence: 99%